2021
DOI: 10.1002/app.51485
|View full text |Cite
|
Sign up to set email alerts
|

Physical modification approaches to enhance cell supporting potential of poly (vinyl alcohol)‐based hydrogels

Abstract: PVA‐based hydrogels with tissue engineered scaffolds application commonly need further modification to improve cell‐matrix interactions with respect to subsequent cell proliferation and differentiation. In this study, PVA‐modified hydrogels were formed by subjecting the solutions of PVA/Poly (R‐3‐hydroxybutyrate) (PHB), PVA/Extracellular Matrix (ECM), and PVA/PHB/ECM to freeze–thaw cycles and additive materials effect on cell supporting potential of the hydrogels was investigated. As, limited cell attachment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…21 In contrast, surface modification methods, which do not alter the bulk structure, overcome these restrictions and considerably improve the primary attachment of cells on scaffolds. 22,23 To provide the biochemical signals necessary for the repair of bone defects, we suggested coating 3D-printed scaffolds with a biomimetic hydrogel made of collagen and biphasic calcium phosphate (BCP) ceramic, which is made from bovine bone (BCP-N) and chemical precursors (BCP-S). We found that the major phases for BCP-N and BCP-S were HA and β-TCP, respectively (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…21 In contrast, surface modification methods, which do not alter the bulk structure, overcome these restrictions and considerably improve the primary attachment of cells on scaffolds. 22,23 To provide the biochemical signals necessary for the repair of bone defects, we suggested coating 3D-printed scaffolds with a biomimetic hydrogel made of collagen and biphasic calcium phosphate (BCP) ceramic, which is made from bovine bone (BCP-N) and chemical precursors (BCP-S). We found that the major phases for BCP-N and BCP-S were HA and β-TCP, respectively (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The PVA solution was then cooled down to 60 °C under magnetic stirring and then cast into the 10 cm petri dishes up to a thickness of 3 mm and exposed to three cycles of freezing and thawing at −80 and 25 °C, for 6 h. PVA hydrogel was prepared according to a former published study. [ 23 ]…”
Section: Methodsmentioning
confidence: 99%
“…Alongside simultaneous measurements with MFM, the characterization of surface roughness through AFM is an important factor that dictates the affinity between cells and the surface of biomaterials. [24][25][26] In this work, we investigated the distribution of magnetic domains in crosslinked poly(vinyl alcohol) (PVA) and sodium alginate (SA) containing MNPs. PVA/SA/MNPs hydrogels were dried in the absence and in the presence of external magnetic field, in order to obtain MNPs distributed randomly (PVA/SA-rMNP) and magnetically oriented MNPs (PVA/SA-gMNP) in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%